Patients’ Perceptions of Health Information Given by Nurses and Clinicians at Discharge at Chiradzulu District Hospital in Malawi, Sub-Saharan Africa - Reuben Solomon Mumba (European Scientific Journal, ESJ, 2018)
Background: Hospital discharge information is a critical component of preparation to facilitate patient transition from hospital to home. Numerous studies elsewhere provide evidence that patients and families encounter a variety of problems after discharge from hospital such as difficulties with functional abilities and carrying out personal care. These problems are often attributed to having unmet informational needs at discharge. Objective: The main objective of the study was to assess patients’ perceptions of the health information provided by nurses and clinicians at discharge. Methods: The study was conducted at Chiradzulu District Hospital in Malawi. A qualitative method of data collection (in-depth interviews) was used. Convenience sampling method was used to select patients into the study. Data was analyzed using Nvivo 9 software. Findings: The study found that most patients were given information by nurses and clinicians on how to perform self-care at home on discharge from hospital. The study revealed that most patients perceived the discharge information as relevant in assisting them with home care. In addition, the study found that most patients perceived it as inadequate. The study also found that the factors that facilitated patients understanding of information were clear explanation of information and use of understandable language by information providers. Barriers included lack of encouragement from information providers to make patients speak, incomprehensive information provided to the patients and patients fear of asking information providers’ questions. Conclusion: Nurses and clinicians should make sure that all patients are given some discharge information to help them to manage their self care at home. Those patients who are at high risk for readmission should be given detailed information.